ARRHYTHMIAS INCLUDING ATRIAL FIBRILLATION CLINICAL COURSE AFTER CORONAVIRUS INFECTION - Sychov, O.S.; Talaieva, T.V.; Nesukay, E.G.; Romanova, O.M.; Getman, T.V.; Ilchyshyna, O.Ya.; Stasyshena, O.V.; Vavilova, L.L. (World of Medicine and Biology, 2022)
This study aimed to determine how coronavirus infection provoked arrhythmias. Fifteen patients with arrhythmias who had coronavirus infection (group C +) and 10 patients who had the same arrhythmias but did not pass through COVID-19 (group C-) were examined. In most cases, atrial fibrillation or atrial flutter dominated in patients of both examined groups – 86.6 % and 80 % appropriately. Age and overweight are risk factors for arrhythmia onset after coronavirus infection. The frequency of paroxysms increased by 88.9 % in patients with AF who underwent coronavirus infection, p